PERBAIKAN KINERJA OPERASIONAL INDUSTRI PENYAMAKAN KULIT DENGAN PENDEKATAN SUPPLY CHAIN DAN LEAN MANUFACTURING (Kasus Industri Kulit Sukaregang) - Muhamad Dzikron; Rakhmat Ceha; Chaznin R Muhammad (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
The industrial sector drive the economy. One of the sub-sectors that have economic potential is a leather and leather garment industry. But the leather industry conditions generally inefficient. In recent years the leather industry there are obstacles to lack of supply of raw materials, and industrial utilization rate is low. Supply of raw materials depend on import of raw leather, medium leather industry utilization during 2010-2015 an average of 50.13%. The low utilization rate reflects the performance of inefficient operation. Responding to the above problems, the approach to lean manufacturing and supply chain management can be applied to improve the performance of the industry. Lean manufacturing in an effort to minimize the efficiency of industrial activities that are not value-added. For the next lean manufacturing approach integrated into industrial relations by the method of Supply Chain so hopefully improve industrial performance and add value. The study begins with business process mapping methods Integrated Definition for Function Modeling (IDEFÃ˜) to identify business processes factually. From the analysis of the process bisniskemudian mapping value chains and identification of critical processes in the leather industry. Furthermore, in design improvements with Lean manufacturing, refers to the concept of value-stream mapping to identify non-value added activities in industrial systems.